The New Art of Breeding Better Dogs - Onstott, Kyle; Revised by Philip Onstott (New York Howell Book House, 1946)
Excellent book for those that are truly into breeding a better breed of dogs. Although originally written in the late 40's and revised/updated in 60's it is still one of the best information on breeding a better dog and the hows and whys of doing it.
Keywords: Dogs--Breeding -- Dogs -- Breeding